Perception Of Using Scripic In Assisting Student's Writing Performance - Shafien, Syakirah; Nik Azim, Nik Ahmad Farhan; Ramamurthy, Lena; Mohd Nawi, Syamimie; Omar, Suhaida; Mohd Nawi, Nur Syahirah (2019)
Learning to write is not an easy task especially when it comes to second language learners. Hence, ScriPic is created based on a collaboration between a series of pictures integrated with the e-learning tool (H5P) to produce a writing essay. It is a picture stimulus teaching innovation that used a sequence of pictures to guide students in their writing. Using this, students are no longer need to use traditional approach where they need to write on paper and only depend on written information given to them. They just need to have an access to the e-learning platform to write their essay. Then, an instant feedback will be given directly to the students for their improvement. It is hoped that this approach can help the students in improving their writing in English.